Abordaje de candidiasis vulvovaginal recurrente mediante restablecimiento de la microbiota vaginal - Hidalgo-Pajuelo, Cristian (2026)
Recurrent vulvovaginal candidiasis (RVVC) is a clinical challenge due to high recurrence and antifungal resistance. We report the case of a 29-year-old woman with over ten years of RVVC unresponsive to conventional antifungal regimens. Vaginal microbiomeanalysis showed severe dysbiosis, with loss of Lactobacillus crispatus and jensenii, and overgrowth of Candida albicans and Prevotella spp. A sequential therapeutic approach was applied: vaginal acidification with boric and lactic acid, recolonization with oral and vaginal probiotics (L. crispatus, jensenii, gasseri), antifungal dietary intervention, and psychological support. Complete symptom resolution was achievedwithin three months, with no subsequent recurrence. This case underscores thepotential role of vaginal microbiota restoration as a complementary therapeutic strategy in refractory RVVC.